Glial fibrillary acidic protein antibody-positive meningoencephalomyelitis. Issue 4 (9th February 2018) - Zarkali, Angeliki; Cousins, Oliver; Athauda, Dilan; Moses, Samuel; Moran, Nicholas; Harikrishnan, Sreedharan
Abstract : Glial fibrillary acidic protein antibody-positive meningoencephalomyelitis is a newly described, possibly under-recognised, severe inflammatory condition of the nervous system. The clinical presentation is variable but most commonly is a combination of meningitis, encephalitis and myelitis; other manifestations may include seizures, psychiatric symptoms and tremor. There is a significant association with malignancies, often occult, and with other autoimmune conditions. Although the disease responds well to corticosteroids acutely, it typically relapses when these are tapered, and so patients need long-term immunosuppression. We report a young man presenting with subacute meningoencephalitis and subsequent myelitis, and discuss the typical presentation and management of this severe but treatable condition.